Deaf clients' experience in accessing health care services in Lilongwe urban - Sabola, Edison Wakale (Kamuzu University of Health Sciences, 2022)
The plight of the deaf patients in accessing the health care services has been a problem especially in the developing countries where proper structures and training of the health personnel on issues of communicating with the deaf patients is still a major challenge. Like any person who is able to hear properly, deaf clients have been experiencing communication problems and isolation by health care workers, as most of them find it difficult to obtain data from patients, as well as giving advice on how to use things like medication. Another concern comes on the issue of lack of privacy as some of the patients need interpreters to express the information to the health personnel. This has led to poor diagnosis being made on the clients leading to wrong prescription of treatment made to those patients. The purpose of this study was to identify the experiences as well as challenges faced by the deaf clients in accessing health services from the health personnel in Lilongwe Urban. A qualitative research design was used whereby a sample of 10 participants were selected randomly and interviewed using an interview guide, with the help of the certified sign language interpreter. Data was analyzed using content analysis.